Phonska Fertilizer Leaching and Its Effect on Spinach Growth and Productivity (Amaranthus tricolor. L) on Latosol with Different Clay Content - Ima Sandra Primanti; Oteng Haridjaja (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2005)
Sufficient available water in soil is very essential for plant growth, not only as a nutrient solvent but also to maintainoptimal turgor pressure. Occasionally, additional water supply from irrigation is necessary to achieve optimal soil water,:ondition. The aim of this research was to study leaching of several nutrients correlated to the growth and productivity ofspinach. PHONSKA fertilizer as a source of nutrients was applied to Latosols Darmaga having different clay content. Thetreatments were subjected to different level of water supply resulting in different soil moisture regime. Factorial completelyrandomized design was used for the experiment; the first factor was clay content. Clay content was differentiated between 81% clay (very fine clayey) and 51 % clay (fine clayey). The secondfactor was level of water supply (100, 120, 140 and 160 % ofwater holding capacity).The result of this research showed that the interaction between clay content and amount of water supplied significantlyinfluenced rate of N, P and K leaching, the sum of leached water and also produced plant biomass (P